PHILOSOPHY OF LAW IN KANT: FOUNDATIONS OF JUSTICE - Martins Sant Anna, Matheus; Massagardi Rodrigues, Fernanda (Revista Gênero e Interdisciplinaridade, 2025)
Immanuel Kant’s philosophy of law represents one of the most consistent theoretical foundations for reflection on justice, particularly for its systematic articulation of freedom, morality, and practical reason. This paper aims to analyze the foundations of justice in Kantian Philosophy of Law, understanding how these elements relate to the structuring of a normative system guided by the autonomy of the will and rationality. The choice of this topic is justified by the permanence and relevance of Kantian thought, which provides conceptual tools for assessing the legitimacy of legal norms, the limits of state action, and the role of institutions in the social order. The relevance of this research lies in the opportunity to deepen the understanding of the principles that underpin the notion of justice and to highlight its contribution to the contemporary legal debate, marked by challenges surrounding the realization of rights and human dignity. The research will be conducted through a bibliographic review, using as central references the Doctrine of Right and the Critique of Practical Reason, as well as commentators who analyze Kant’s work from a legal and philosophical perspective. The method will allow us to reconstruct and interpret the main concepts formulated by Kant, systematizing their relationships and implications. Among the study’s potential contributions are the systematization of foundations that remain relevant to law, the strengthening of the debate on justice on rational grounds, and the provision of support for critical reflection on the legitimacy of legal norms and institutions today.